1993
DOI: 10.1021/ma00066a022
|View full text |Cite
|
Sign up to set email alerts
|

Early-stage phase separation in polyimide precursor blends: an atomic force microscopy study

Abstract: The surface of polyimide precursor blends is studied using atomic force microscopy (AFM). The acid (PAA) and ester (PAETE) precursors in the blends are of the same polyimide. The topographical contrast is due to the complexation of solvent with the acid precursor, causing the latter to swell. Early-stage phase separation prior to impingement is studied for a blend with 20% weight fraction of PAA relative to PAETE. The growth rate of the domains is by nucleation and growth. The PAA-rich discontinuous phase grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…A TOMIC FORCE MICROSCOPY (AFM) has been applied in the surface analysis of polymeric materials on a nanometer scale [1][2][3][4][5][6]. Haeringen et al have used AFM to investigate the morphology, filler distribution, and adhesion of elastomers using chemically modified tips [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A TOMIC FORCE MICROSCOPY (AFM) has been applied in the surface analysis of polymeric materials on a nanometer scale [1][2][3][4][5][6]. Haeringen et al have used AFM to investigate the morphology, filler distribution, and adhesion of elastomers using chemically modified tips [7].…”
Section: Introductionmentioning
confidence: 99%
“…The blends show characteristics of fluororsilicone rubber [11]. Using AFM, Ghosh et al [12] have reported that the surface of the unfilled fluororubber is smooth except for the randomly distributed Ca(OH) 2 particles, which are present in the formulation as potential acid acceptor. Silicone rubber surface, on the other hand, possesses a granular morphology and the blends of silicone rubber and fluororubber are microheterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…We note that initially, a.s PAA -» Pl(l), the depth of the dimples is reduced because of CPAARP shrinkage, but the elevation difference is enhanced during the second process of PAETE -^ PI(2). 448 and 6(c) is not as sipiflcant on curing for PAETE-rich blends [38].…”
Section: Adhesion Enhancementmentioning
confidence: 93%
“…[A blend of x% PAA andyVc = (100 -JC) PAETE is referred to asjc/y.] The minority component (PAA) forms the discontinuous PAA-rich phase (DPAARP) that is elevated with respect to the continuous PAETE-rich matrk (CPATRP) with excess NMP [38]. The uniform size distribution of the DPAARP "mounds" is due to phase separation by spinodal decomposition.…”
Section: Adhesion Enhancementmentioning
confidence: 99%
“…or alloys of these metals is employed as an adhesion-promoting layer [4,5] or a seed layer [6,7]. The application of these adhesion-promoting layers requires deposition equipment and a number of process steps.…”
mentioning
confidence: 99%